Developing a Framework and Pedagogies for the Delivery of Remote Accessible Laboratory Systems in Science and Engineering - Mohammadi, Nazanin (Curtin University, 2021)
The teaching and learning methods applied to the in-person classroom are not entirely capable of addressing the requirements for an online laboratory environment. The aim of the study is to create the pedagogies for remote laboratories. Therefore, a test environment was developed and user observations were captured over four years. This research proposed an educational framework for online science and engineering laboratory and summarized the most significant aspects to be included in the laboratory design.